A Narrative Approach to Describe QoL in Children With Chronic ITP - Giordano, Paola; Lassandro, Giuseppe; di Meo, Nicola Antonio; Palladino, Valentina; Lovrencic, Barbara; Spinelli, Marco; Reale, Luigi; Jankovic, Momcilo (Frontiers in Pediatrics, 2019)
Objective: Primary immune thrombocytopenia (ITP) is a hemorragic disorder. Spontaneous recovery within 6 months occurs in the majority of pediatric patients. Nevertheless, in 20–30% of children the disease is chronic. The impact extends to the patients' families, whose everyday life, in terms of interpersonal relationships and financial status, is adversely affected. This study investigated the ability of a narrative instrument to improve the quality of life of pediatric chronic ITP patients and their families and quantified the familial burden imposed by the illness. Method: A quantitative survey and a narrative plot delivered through an online platform were adopted for the analysis. Results: Ten Italian Hematologic Centres publicized the project to patients in their waiting rooms, and 70 caregivers of children with ITP answered the ad-hoc questionnaire. Data from 53 caregivers revealed the emotional impact of pediatric chronic ITP. The narrative approach was able to highlight the specific resources used by patients and their families to cope with the disease and its chronicity. Conclusions: Caregivers underlined the need for “humanity” in their interactions with clinical personnel. The majority of respondents provided positive feedback regarding the narrative project, defining the experience as “liberating” and improving their quality of life.